Corporate environmental disclosures in Malaysian public listed companies - Phua, Siew Huei Michelle (Curtin University, 2016)
This thesis investigates the impact of board gender diversity in influencing board decision to communicate environmental information in annual reports of Malaysian listed companies in year 2013. Legitimacy theory is used as the theoretical framework to explain the association between board gender diversity and the extent of corporate environmental disclosure by Malaysian companies. Findings of this study reveal that there is a statistically significant association between presence of female directors in corporate boardroom and female directors holding multiple directorships on the extent of corporate environmental disclosure by Malaysian companies. Overall, the findings of this thesis can be used as a driver to encourage more female participation in decision making and communication processes of public listed companies and there is also a need to enforce and mandate disclosure of environmental information in annual reports of Malaysian listed companies.